A graphical user interface to approximate area (AMOEBA) using trapezoidal method for teaching and learning processes / Nurul Ain Johar ... [et al.] - Johar, Nurul Ain; Norhisham, Nurul Hazirah; Nasir, Mohd Agos Salim; Soid, Siti Khuzaimah; Md Tahir, Herniza (Universiti Teknologi MARA, Kedah, 2023)
The trapezoidal method plays a crucial role in mathematics and numerical analysis for approximating the area under a curve. We present a user-friendly Graphical User Interface (GUI) designed for educational purposes to facilitate effective teaching and learning of this method. The GUI provides an interactive platform that engages students and educators in a visually appealing and user-friendly environment. The GUI's features improve teaching and learning. Students may enter functions and choose approximation intervals. The interface shows the curve and trapezoids that approximate its area. Students may see how changing the number of trapezoids affects approximation accuracy. The GUI allows real-time function and interval modifications for clarity. This lets students see how function changes affect estimated area. The GUI provides fast feedback and allows comparisons with known precise solutions by displaying the estimated area numerically. Experimental learning is encouraged by the GUI. Students may explore functions and intervals, notice the approximations, and compare the results. This hands-on approach helps comprehend the trapezoidal technique and its practical applications. The interface's graphics enhances learning. Visualizing trapezoidal approximation helps students understand the math. The GUI also helps educators convey the trapezoidal approach graphically, helping students understand the material. The proposed Graphical User Interface for teaching and learning the trapezoidal method is an effective educational aid for numerical analysis in general. Through its interactive features, real-time visualizations, and user-friendly layout, the GUI facilitates comprehension, inquiry, and engagement, ultimately augmenting the learning experience and fostering a deeper comprehension of the trapezoidal method and its applications.